The dependence of radar target detectability on array weighting function - Alabaster, Clive M.; Hughes, Evan J. (Cranfield University, 2009)
This paper describes simulation work to assess the detectability of targets by an airborne fire control radar (FCR) operating in a medium pulse repetition frequency (PRF) mode in the presence of strong ground clutter as a function of transmitting and receiving array weighting functions.
Presented at the IET-Radar 2007 Conference Edinburgh 15-18 October 2007
Keywords: Radar detection; Clutter; Medium PRF; Illumination function.; Pulse Repetition Frequency